The Strength of the Geomagnetic Field at the Cretaceous-Tertiary Boundary: Palaeointensity Results from the Deccan Traps(India)and the Disko Lavas(Greenland). (Dataset) ... - J. SHAW; G. J. SHERWOOD; A. E. MUSSETT; T. C. ROLPH; K. V. SUBBARAO; P. V. SHARMA (Magnetics Information Consortium (MagIC), 2007)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: The Strength of the Geomagnetic Field at the Cretaceous-Tertiary Boundary: Palaeointensity Results from the Deccan Traps(India)and the Disko Lavas(Greenland). ...